THE ANALYSIS RELEVANCY CHARACTER VALUES OF THE NOVEL SANG PENCERAH/THE ENLIGHTER IN CHARACTER EDUCATION AT PPMI/PONDOK PESANTREN MODERN ISLAM ASSALAM (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The main targets of the research are to study and describe: 1. The Character values of the Novel Sang Pencerah/The Enlighter; 2. The Character education implementation at PPMI Assalaam; 3. The relevancy character values of the Novel Sang Pencerah/The Enlighter in character education at PPMI Assalaam. This research uses qualitative approach with phenomenology design. Data gathering technique uses are: in-depth interview, observation, and documentation. Data validity technique uses triangulation. Data analysis uses interactive model. The research results showed that: 1. There are eighteen (18) characters values that have been found in Novel Sang pencerah/The enlighter and also at PPMI Assalaam. Those characters are: religius, honest, tolerance, disipline, work hard, creative, independence, democration, curiousity, spirit, of nationalsm, country’ love, achivement appreciation, communicative/closed friends, peace and reading hobby/love, take care of environment and social, responsibility. 2. Implementation 3. The character values Relevancy of the novel sang pencerah/The Enlighter in character education at PPMI Assalam There is empathyi relevancy that has been found between character education in Sang Pencerah/The Enlighter and character education in PPMI Assalaam: The first is principal relevancy, there are three principles similarity. 1.Tauhid Principle that is stated The Inner Most of High Allah SWT. 2. Modern, that means adapted, commodative fund towards the new ideas, both that are sources from in community/country or out of community/oversea. 3. Eegalitarian means: all of the people is same, the different is in ketaqwaan/surrendering towards Allah SWT. The second relevancy is the goal, both have the same goal that is create Islamic generation who have the great attitude and behavior/ahlakul karimah/the best people based on Al-Quran and As-Sunnah. The third relevancy is the content, it means that the values of character education that is found in both is almost the same. (4) The way relevancy. The way of teaching learning character education both of them is the same.  Such as: giving suggestion through speech, dialog or discussion, habituality, leadership, good example and learning that based on problem solving.